THE ROLE OF PUMPKIN SEED OIL AS A THERAPY FOR TYPE 2 DIABETES MELLITUS - Suwanto, -; Widiyanto, Slamet; Daryono, Budi Setiadi; Retnoaji, Bambang; Widodo, Harto (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Type 2 diabetes mellitus is a very common non-communicable disease; the prevalence of diabetes is growing every year. Treatments of diabetes are based on lifestyle modification and oral and injectable drug therapy. Drug therapies have a negative impact on the body. Most patients began to switch to natural ingredients as antihyperglycemic, namely pumpkin seeds. The content of pumpkin seed oil is fatty acids, consisting of oleic acid, linoleic acid, lauric acid, palmitic acid, and stearic acid. Objective: To explore the potential of pumpkin seed oil and especially as a therapy for type 2 diabetes mellitus. Methods: The is a narrative review done through extensive literature search, identification, search, and download of national and international journal references. Literature studies were conducted through several portals, such as PubMed, Elsevier, ScienceDirect, and Google Scholar. The references that had been found were in accordance with the predetermined inclusion criteria. Articles were not used if the topic was not relevant. The search for references was in the form of research journals published on the internet for the last 10 years from 2013-2024. Results: (1) pumpkin and content, the results of the Cucurbitaceae family pumpkin, has a fatty acid content (linoleic, oleic, stearic, and palmitic). (2) linoleic acid on protein tyrosine phosphatase inhibition, the results can provide antidiabetic effects to prevent type 2 diabetes. (3) oleic acid on insulin hormone balance, the results of protection in diabetes mellitus by accelerating GLP-1 secretion. (4) Oleic acid on pancreatic beta cell function, results in securing insulin sensitivity by suppressing ROS formation and regulating MMP-2 activity in cell line 1.1B4. (5) Oleic acid on antioxidant, protective results on structural damage and function of antioxidant enzymes associated in hyperglycemia. (6) lauric acid stimulates GLP-1, results in increased proliferation activity and decreased apoptosis of beta cells. (7) lauric acid as diabetic wound healing, results play a role in improving wound healing because it can stimulate angiogenesis and suppress inflammatory markers. (8) palmitic acid on insulin and beta cell activity, results palmitic acid plays an important role in insulin control and beta cell activity. (9) stearic acid as a tyrosine phosphatase 1B inhibitor, the results of stearic acid increase receptor signaling to stimulate glucose uptake. Conclusion: Pumpkin seed oil contains potential fatty acids and acts as a therapy for diabetes mellitus. The potential and role as a therapy for diabetes is due to the content of pumpkin seed oil known to have activity in balancing insulin hormones, pancreatic beta cell function, antioxidants, stimulating Glucagon like peptide-1, and healing diabetic wounds. International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 13-21